Relationship between the Parameters of the Second Virial Coefficient of Non-Abelian Anyons and the Two-Parametric Fractional Statistics - Sobko, B.Yu. (Ukrainian Journal of Physics, 2021)
A relationship between the parameters of the second virial coefficient for the system of non- Abelian anyons and two-parametric modifications of the Haldane–Wu and Polychronakos fractional statistics has been demonstrated. Parameters that can approximately describe non-Abelian anyons using the indicated statistics types are calculated. The limit at which the non-additivity/incompleteness parameter q tends to unity is considered.